Surgical indication for pontine hemorrhages: From the analysis of 4 surgically and 2 medically treated cases - Hamajima, Izumi; Tsuchida, Hiromi; Kitami, Koichi; Sohma, Tsutomu; Takeda, Tamotsu (Japanese Journal of Stroke, 1987)
Six cases of primary pontine hemorrhage were reported and each of their clinical test results were compared from the standpoint of making the indication for radical operation. Four cases were performed the surgical removal of the hematoma. In three of them, surgery was done in the acute phase (2-4 days), the other one got the surgery in the subacute phase (19 days). Their preoperative consciousness were worse than semicoma, with disturbance of respiration and decerebrate posture. In all surgical cases, the respiratory care became much easier after the operation, and amelioration in consciousness were obtained in three cases. Although one case expired of myocardial infarction, none of them died of surgical insults. In one surgical case, auditory brainstem response (ABR) and continuous intracranial pressure (ICP) recording suggested the enlargement of hematoma with marked obstructive hydrocephalus, and clearly showed the timing for the radical operation. Two cases were treated medically. One case showed normal ABRs on one side and made the dramatic recovery from coma to alertness. But his activity of daily life was not so satisfactory even 6 months later. Another case was a typical fulminant type, who died of brainstem damage one month after the onset. In conclusion, the surgical indication for pontine hemorrhages was thought as below. I : Life saving indication -When deterioration in ABR and/or enlargement of hematoma in CT occur which cause secondary ischemic damage to the residual brainstem function. II : Functional indication -When ABRs are normal on at least one side and tendency of recovery in consciousness appeares. The operative procedure (craniotomy or burr-hole irrigation like CT-guided method) was thought to be controversial. Among the diagnostic tests, ABR and ICP monitoring were considered mostly valuable methods on managing the treatment of pontine hemorrhages.